STRATEGI MANAJEMEN DALAM MENINGKATKAN PRESTASI BELAJAR SISWA - Abdullah Ali (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2021)
This study aims to determine management strategies for improving student achievement. The research method used in this study was a descriptive analysis. The research approach used was qualitative. Data collection techniques were carried out the library research method. The results showed that the management strategy to improve student performance is to monitor all routine activities that occur every day. The principal carries out daily leadership activities that are environmentally friendly, familial, and democratic and always prioritizes cooperation rather than selfishness for the benefit of students and all staff. Principals are also involved to assist teachers, staff, and employees in monitoring student success. In addition, as a pioneer in improving student achievement, school leaders become a top priority in the teaching and learning process.